Influences of the 1855 AD Huanghe (Yellow River) Relocation on Sedimentary Organic Carbon Burial in the Southern Yellow Sea - Liu, Jianying; Li, Da-Wei; Ding, Yang; Ge, Tiantian; Chen, Weifang; Huh, Chih-An; Zhao, Meixun (Frontiers in Marine Science, 2022)
The Huanghe (Yellow River) supplies large amount of sediments and terrestrial organic carbon (OC) to the eastern Chinese marginal seas. A relocation of the Huanghe outlet from the southern Yellow Sea (YS) to the Bohai Sea occurred in 1855 AD, however, detailed knowledge about the impact of this relocation on sedimentary source and OC burial in Chinese marginal seas is still critically lacking. In this study, we present total OC content and its isotope (δ13C), along with bulk total organic carbon (TOC)/total nitrogen (TN) molar ratio and lipid biomarker contents, in a sediment core HH12 from the southern YS with sediment age spanning the last 300 years. We find that TOC and terrestrial lipid biomarker mass accumulation rates were lower between 1855 AD and 1950 AD than that prior to 1855 AD in core HH12; and in accordance, both TOC/TN ratio and δ13C records indicate a gradual decrease of terrigenous source contributions to sedimentary OC. This suggests that the relocation of the Huanghe outlet reduced the transport of terrestrial OC to the southern YS. However, the δ13C record also indicates a relative increase of terrestrial OC contribution to sedimentary OC after 1950 AD, and the most likely explanation is increased contributions from the old Huanghe delta erosion and Korean rivers. Future studies should focus on better constraining the variations of terrestrial and marine endmembers with δ13C and Δ14C analyses of specific biomarkers to examine these linkages.